Diversifikasi layanan pada layanan Sapa Pustakawan di Perpustakaan IAIN Kudus - Radiya Wira Buwana (FPPTI Jawa Tengah, 2022)
Diversification of library services is an effort to diversify library services. This effort is carried out in order to create library services that are appropriate and in accordance with the needs of the users it serves. This research aims to find out how to diversify services in the Sapa Pustakawan service at the IAIN Kudus Library. The research method used in this research is descriptive qualitative methods. The data collection method used in this research is through observation and literature study methods. The data collection method through observation was carried out by researchers to observe and collect data regarding the implementation of the Sapa Pustakawan service at the IAIN Kudus Library. Meanwhile, researchers use the literature study method to collect data about references related to the research theme. The data obtained in this research was then analyzed and presented using qualitative data analysis techniques. From this research it can be concluded that the Sapa Pustakawan service has been able to carry out service diversification well. The diversification of services in the Sapa Pustakawan service is based on the increasingly diverse needs of users and the increasingly rapid advances in information technology. Through service diversification, several service products have been created from the Sapa Pustakawan service. Products from the diversification of services in the Sapa Pustakawan service at the IAIN Kudus Library include the Onsite Sapa Pustakawan service, the Online Sapa Pustakawan Service, the roving reference service, and the Zotero class service.